IMPLEMENTASI E-GOVERNMENT DALAM PELAYANAN PUBLIKSTUDI KASUS: PEMBUATAN E-KTP DI JAKARTA TIMUR DAN JAKARTA PUSAT - Muhammad Yohan Surya Y (2022)
Public services carried out by the government are one of the important things because the citizen always use these services to meet their needs. The development of technology and information is so rapid and has entered various sectors of life, be it in the socio-economic, cultural, educational, or government fields. These technological advances also help in the government sector in providing services to the community, the use of technology and information in the field of government, commonly known as e-government. Utilization of e-Government should be utilized as well as possible in providing public services. In this paper, I want to see how the service for making e-KTPs is in the East Jakarta Dukcapil and Central Jakarta Dukcapil. Considering that according to 2019 BPS data, East Jakarta is the area with the most dense population compared to other Jakarta areas. In addition, Central Jakarta is the heart of the capital, because many government offices are located in Central Jakarta. Departing from that, the author feels it has an urgency to examine how the implementation of e-Government in the service of making e-KTP in the Dukcapil East Jakarta and Central Jakarta. This research is a research with a qualitative approach, and the data obtained by in-depth interviews. The analytical knife used in this research is the theory of Electronic Service quality or what is often called eServqual. The results showed that the quality of e-Government services in making e-KTP both in the East Jakarta Dukcapil and Central Jakarta Dukcapil still encountered several obstacles. The obstacles are: (1) Lack of socialization provided; (2) facilities and infrastructure that are less supportive; and (3) Lack of sufficient human resources (HR).